Inactivated Lactobacillus plantarum Carrying a Surface-Displayed Ag85B-ESAT-6 Fusion Antigen as a Booster Vaccine Against Mycobacterium tuberculosis Infection - Kuczkowska, Katarzyna; Copland, Alastair; Øverland, Lise; Mathiesen, Geir; Tran, Andy C.; Paul, Mathew J.; Eijsink, Vincent G. H.; Reljic, Rajko (Frontiers in Immunology, 2019)
Vaccination is considered the most effective strategy for controlling tuberculosis (TB). The existing vaccine, the Bacille Calmette-Guérin (BCG), although partially protective, has a number of limitations. Therefore, there is a need for developing new TB vaccines and several strategies are currently exploited including the use of viral and bacterial delivery vectors. We have previously shown that Lactobacillus plantarum (Lp) producing Ag85B and ESAT-6 antigens fused to a dendritic cell-targeting peptide (referred to as Lp_DC) induced specific immune responses in mice. Here, we analyzed the ability of two Lp-based vaccines, Lp_DC and Lp_HBD (in which the DC-binding peptide was replaced by an HBD-domain directing the antigen to non-phagocytic cells) to activate antigen-presenting cells, induce specific immunity and protect mice from Mycobacterium tuberculosis infection. We tested two strategies: (i) Lp as BCG boosting vaccine (a heterologous regimen comprising parenteral BCG immunization followed by intranasal Lp boost), and (ii) Lp as primary vaccine (a homologous regimen including subcutaneous priming followed by intranasal boost). The results showed that both Lp constructs applied as a BCG boost induced specific cellular immunity, manifested in T cell proliferation, antigen-specific IFN-γ responses and multifunctional T cells phenotypes. More importantly, intranasal boost with Lp_DC or Lp_HBD enhanced protection offered by BCG, as shown by reduced M. tuberculosis counts in lungs. These findings suggest that Lp constructs could be developed as a potential mucosal vaccine platform against mycobacterial infections.